Some aspects of deposition of conductive, dielectric and protective coatings on insulators with using arc discharge dc and RF bias - Taran, V.S.; Muratov, R.M.; Nezovibat'ko, Y.N.; Leonovych, A.V.; Sergiiets, M.A. (Вопросы атомной науки и техники, 2017)
Investigation results for technological process of low temperature plasma deposition of functional coverings for dielectric substrate at low temperatures (50…250 oC) are shown. Combined high frequency and arc plasma sources were used to provide high deposition rate and an opportunity to operate with heat sensitive substrate such as plastic, glass etc. Using this method there were obtained: pads on detectors of ionizing radiation, optically transparent protecting coverings for plexiglass, connecting coverings on mica for ultra-frequency emitter. Показаны результаты исследования технологического процесса низкотемпературного плазменного осаждения функциональных покрытий для диэлектрической подложки при низких температурах (50…250 °С). Для обеспечения высокой скорости осаждения и возможности работать с теплочувствительными подложками, такими как пластик, стекло, были использованы комбинированные высокочастотные и дуговые источники плазмы. С помощью этого метода были получены: детекторы ионизирующего излучения, оптически прозрачные покрытия для плексигласа, соединительные покрытия на слюде для ультрачастотного излучателя. Показано результати дослідження технологічного процесу низькотемпературного плазмового осадження функціональних покриттів для діелектричної підкладки, при низьких температурах (50…250 °С). Комбіновані високочастотний і дуговий джерела плазми були використані для забезпечення високої швидкості осадження і можливість працювати з теплочутливою підкладкою, такою як пластик, скло і т. д. За допомогою цього методу були отримані: детектори іонізуючого випромінювання, оптично прозорі захисні покриття для плексигласу, з'єднувальні покриття на слюді для ультрачастотного випромінювача.